Long-term outcomes and lymph node metastasis following endoscopic resection with additional surgery or primary surgery for T1 colorectal cancer - Pin-Chun Chen; Yi-Kai Kao; Po-Wen Yang; Chia-Hung Chen; Chih-I Chen (Scientific Reports)
Abstract Optimal management of T1 colorectal cancer (CRC) remains controversial. This study compared the long-term outcomes of endoscopic resection with additional surgical resection (ER + ASR) versus primary surgical resection (PS) in patients with T1 CRC and identified risk factors for lymph node metastasis (LNM). This retrospective cohort study included 373 patients with T1 CRC who underwent ER + ASR or PS between January 2010 and December 2020 at a tertiary center in Taiwan. Surgical and oncological outcomes, including recurrence rates, LNM, 5-year overall survival (OS), and 5-year recurrence-free survival (RFS) were compared. Univariate and multivariate analyses identified risk factors for LNM. No significant differences were observed between the ER + ASR and PS groups in surgical outcomes, recurrence rates, LNM, 5-year OS (93% vs. 89%, P = 0.18), or 5-year RFS (89% vs. 88%, P = 0.47). Patients with ≥ 2 high-risk factors had significantly lower 5-year OS and RFS compared to those with ≤ 1 risk factor (p < 0.01). Poor histology grade and lymphovascular invasion were independent risk factors for LNM. ER + ASR and PS had comparable long-term outcomes in patients with T1 CRC. A multidisciplinary approach and standardized protocols are required for optimal management of early-stage CRC.